Amelogenin-assisted ex vivo remineralization of human enamel: effects of supersaturation degree and fluoride concentration - Fan, Yuwei (2011)
The formation of organized nanocrystals that resemble enamel is crucial for successful enamel remineralization. Calcium, phosphate and fluoride ions and amelogenin are important ingredients for the formation of organized hydroxyapatite (HAP) crystals in vitro. However, the effects of these remineralization agents on the enamel crystal morphology have not been thoroughly studied. The objective of this study was to investigate the effects of fluoride ions, supersaturation degree and amelogenin on the crystal morphology and organization of ex vivo remineralized human enamel. Extracted third molars were sliced thin and acid-etched to provide the enamel surface for immersion in different remineralization solutions. The crystal morphology and mineral phase of the remineralized enamel surface were analyzed by FE-SEM, ATR-FTIR and XRD. The concentration of fluoride and supersaturation degree of hydroxyapatite had significant effects on the crystal morphology and crystal organization, which varied from plate-like loose crystals to rod-like densely packed nanocrystal arrays. Densely packed arrays of fluoridated hydroxyapatite nanorods were observed under the following conditions: σ(HAP) = 10.2±2.0 with fluoride 1.5±0.5 mg/L and amelogenin 40±10 µg/mL, pH 6.8±0.4. A phase diagram summarized the conditions that form dense or loose hydroxyapatite nanocrystal structures. This study provides the basis for the development of novel dental materials for caries management.